1989
DOI: 10.1093/oxfordjournals.eurheartj.a059431
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of propranolol and amiodarone in suppressing ventricular arrhythmias following myocardial infarction

Abstract: The purpose of this prospective randomized trial was to compare the efficacy of propranolol and amiodarone in suppressing ventricular arrhythmias during the first 6 months following myocardial infarction (MI). 97 patients were treated with either amiodarone (n = 48) or propranolol (n = 49) starting on the 9th day following MI. Holter monitoring was carried out on four occasions: on D7, D21, D90 and D180. There was no statistical difference in the incidence of 'major' arrhythmias (an average of at least 10 vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Two trials have compared amiodarone to pure beta-blockers (metoprolol or propranolol) and reported that amiodarone is superior to beta-blockers in suppressing ventricular ectopic beats on Holter monitoring [37,38] . However, it is becoming increasingly apparent that suppression of ventricular ectopic beats on Holter monitoring does not correlate with a beneficial effect on the recurrence of spontaneous sustained ventricular tachyarrhythmia [30,31,39] .…”
Section: Efficacy Of Sotalol and Amiodarone In Preventing Death From mentioning
confidence: 99%
“…Two trials have compared amiodarone to pure beta-blockers (metoprolol or propranolol) and reported that amiodarone is superior to beta-blockers in suppressing ventricular ectopic beats on Holter monitoring [37,38] . However, it is becoming increasingly apparent that suppression of ventricular ectopic beats on Holter monitoring does not correlate with a beneficial effect on the recurrence of spontaneous sustained ventricular tachyarrhythmia [30,31,39] .…”
Section: Efficacy Of Sotalol and Amiodarone In Preventing Death From mentioning
confidence: 99%